Peran Guru Dalam Implementasi Kurikulum Merdeka di Indonesia: Kasus di Sekolah Dasar Islam di Indonesia - Ahillah, Ade Irma; Shaefah, Milkhahtus; Ghufron, M Ali (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2023)
This study aims to describe and analyze phenomena, events, social activities, attitudes, beliefs, perceptions, and thoughts of individuals and groups regarding the role of teachers in implementing a freedom curriculum. This study uses a phenomenological approach. This type of research is qualitative research that sees and hears more closely and in detail the individual's explanations and understanding of his experiences. The phenomenological approach is based on researchers' interest in examining the phenomena experienced by key informants more deeply. The research was conducted at MINU Buaran. The informants in this study were teachers and heads of madrasas. Data collection is carried out by several techniques, namely observation, interviews, and documentation studies. The results of this study concluded that implementing a freedom curriculum is a key factor in the world of education that must be ready and able to follow the development of science and technology, especially those related to education. It is undoubtedly not easy to create an atmosphere of learning effectively and maximally if you look at the role of the teacher, which is increasingly complex and the students' reaction when receiving learning is also one of the important factors demi manifested high achievements in learning. This is what makes a freedom curriculum to learn.